If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -8 = 8y Reorder the terms: -8 + 6y = 8y Solving -8 + 6y = 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. -8 + 6y + -8y = 8y + -8y Combine like terms: 6y + -8y = -2y -8 + -2y = 8y + -8y Combine like terms: 8y + -8y = 0 -8 + -2y = 0 Add '8' to each side of the equation. -8 + 8 + -2y = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -2y = 0 + 8 -2y = 0 + 8 Combine like terms: 0 + 8 = 8 -2y = 8 Divide each side by '-2'. y = -4 Simplifying y = -4
| 6x^2-7x-3= | | 5m^2-17n=-6 | | 6x-9=4x+17 | | 4(5j+3k^2)-18j-13k^2-(-k^2+j)= | | 3x^2+4x-4= | | 9x^2-270=0 | | 25=100-250 | | 4x+7=x+25 | | -5x+45-89=-90+41 | | 25x+11-.1x=18.50 | | 2(3u-7)=16 | | 2x^3-5x=12 | | -x^2+8x+4=5 | | 12X^2=24X | | 21d-4=14 | | 3x+2x+4=29 | | 2X^2-3X=9 | | 5(x-2)=4-2(3x-4) | | 2x=3x-4 | | 7x=5y+12 | | 3a+34=5a-4 | | 4x^2+3x-8=0 | | 3x-10+13=-2x+28 | | -3x+5=7x+8 | | 3x^2-11x-10=0 | | x^2+3=2x | | 3x^3-11x-10=0 | | k^2=21 | | x^2-10=3 | | k^2=4 | | -5z+9z=-2z-2-9z | | 2(x+5)+3=7 |